Implementing a Treat‐to‐Target Approach for Rheumatoid Arthritis During the COVID‐19 Pandemic: Results of a Virtual Learning Collaborative Program. Issue 4 (4th February 2022) - Solomon, Daniel H.; Pincus, Theodore; Shadick, Nancy A.; Stratton, Jacklyn; Ellrodt, Jack; Santacroce, Leah; Katz, Jeffrey N.; Smolen, Josef S.
Abstract : Objective: A treat‐to‐target (TTT) approach improves outcomes in rheumatoid arthritis (RA). In prior work, we found that a learning collaborative (LC) program improved implementation of TTT. We conducted a shorter virtual LC to assess the feasibility and effectiveness of this model for quality improvement and to assess TTT during virtual visits. Methods: We tested a 6‐month virtual LC in ambulatory care. The LC was conducted during the 2020–2021 COVID‐19 pandemic when many patient visits were conducted virtually. All LC meetings used videoconferencing and a website to share data. The LC comprised a 6‐hour kickoff session and 6 monthly webinars. The LC discussed TTT in RA, its rationale, and rapid cycle improvement as a method for implementing TTT. Practices provided de‐identified patient visit data. Monthly webinars reinforced topics and demonstrated data on TTT adherence. This was measured as the percentage of TTT processes completed. We compared TTT adherence between in‐person visits versus virtual visits. Results: Eighteen sites participated in the LC, representing 45 rheumatology clinicians. Sites inputted data on 1, 826 patient visits, 78% of which were conducted in‐person and 22% of which were held in a virtual setting. Adherence with TTT improved from a mean of 51% at baseline to 84% at month 6 ( P for trend < 0.001). Each aspect of TTT also improved. Adherence with TTT during virtual visits was lower (65%) than during in‐person visits (79%) ( P  < 0.0001). Conclusion: Implementation of TTT for RA can be improved through a relatively low‐cost virtual LC. This improvement in TTT implementation was observed despite the COVID‐19 pandemic, but we did observe differences in TTT adherence between in‐person visits and virtual visits.